2014
DOI: 10.1177/239700221402800106
|View full text |Cite
|
Sign up to set email alerts
|

Leadership Behavior as a Health-Promoting Resource for Workers in Low-Skilled Jobs and the Moderating Role of Power Distance Orientation

Abstract: In this study, the authors analyze leadership behaviors as potential health-promoting resources for low-skilled workers in a highly culturally diverse work setting. The authors hypothesize that subordinates' and supervisors' individual power distance orientations will moderate the effect of subordinates' perceptions of leadership behavior and the subsequent effects on their well-being. Multilevel modeling is used to analyze a sample of data from 474 low-skilled employees (50% immigrants) and 35 direct supervis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 64 publications
1
28
0
Order By: Relevance
“…In a qualitative study with low-skilled workers and first-level supervisors, Winkler, Busch, and Duresso (2013) found that social support, positive feedback, and task-related communication by supervisors were concrete behaviors that were able to improve the job satisfaction and well-being of employees in low-skilled jobs. This finding was subsequently confirmed in a cross-sectional study on low-skilled workers and their supervisors (Winkler, Busch, Clasen, & Vowinkel, 2014).…”
Section: Health-promoting Leadership Behaviormentioning
confidence: 63%
See 1 more Smart Citation
“…In a qualitative study with low-skilled workers and first-level supervisors, Winkler, Busch, and Duresso (2013) found that social support, positive feedback, and task-related communication by supervisors were concrete behaviors that were able to improve the job satisfaction and well-being of employees in low-skilled jobs. This finding was subsequently confirmed in a cross-sectional study on low-skilled workers and their supervisors (Winkler, Busch, Clasen, & Vowinkel, 2014).…”
Section: Health-promoting Leadership Behaviormentioning
confidence: 63%
“…Various dimensions of communication-in particular, job-relevant communication from a superiorare positively associated with subordinate job satisfaction and negatively related to subordinate burnout (Kim & Lee, 2009;Miles et al, 1996). Finally, positive feedback by supervisor has been found to relate positively to low-skilled worker's well-being (Winkler et al, 2013;Winkler et al, 2014). A supervisor who communicates positive feedback to the individual employee enhances self-esteem as important aspect of wellbeing of the employee (Ashford & Cummings, 1985;Kelloway, Weigand, McKee, & Das, 2012).…”
Section: Health-promoting Leadership Behaviormentioning
confidence: 99%
“…Their diary study shows, amongst other things, that person-level servant leadership (controlling for day-level emotional dissonance) has a positive impact on day-level ego depletion and need for recovery. In a similar vein, both Stocker et al (2014) and Winkler et al (2014) show that when leaders provide social support, task-related communication, and appreciative feedback (in the form of simple praise and gratitude) this has a positive impact on employees' well-being -even for workers in low-skilled jobs working on poorly designed tasks. Gregersen et al (2014) go further to investigate the question of which specific forms of leader behavior are most effective in promoting well-being and preventing burnout.…”
Section: Pathway 1: Leaders As Initiators Of Direct Person-focused Acmentioning
confidence: 95%
“…The latter would be useful to explore because (depending on one's metatheoretical orientation) it would seem plausible that factors such as personality or shared social identity can partly determine whether specific supervisor behaviours (passive, constructive or destructive) serve to help or harm the health of employees (see Benolil & Somech, 2014). Indeed, speaking to such possibilities, Winkler et al (2014) report intriguing interactions between the power distance of supervisors and employees which suggest that issues of leader-subordinate fit have a bearing on health outcomes.…”
Section: Pathway 1: Leaders As Initiators Of Direct Person-focused Acmentioning
confidence: 99%
“…However, many organizations seem to neglect the contribution of the managers to employees' stress, and stress-related illnesses [1]. Therefore, managers are recommended to raise the awareness of the influence their leadership style exerts on employees' health [24].…”
Section: Discussionmentioning
confidence: 99%